Direct Marketing sebagai Strategi Komunikasi Pemasaran dalam Produk Pakaian "Embrio" - Fauzi, Mufti (Jurnal Inovasi Komunikasi, 2024)
Abstract. This research begins with the growth of “Embrio”  distro to survive on the competition of clothing distro product with the marketing strategy that was initially conventional, then switch with direct marketing method using existing media channels. The purpose of this research is to know the interactivity of customer relationship, to know how “Embrio”  distro using media channel in direct marketing and know the pull factor and the impetus to do direct marketing as a means of promotion in marketing “Embrio”  distro. Theories used are Marketing Communication Theory, direct marketing and symbolic interaction. This research was conducted at “Embrio”  Clothing Distro at Plaza Parahyangan Bandung. And as key informant is the owner and an employee. This research uses a case study method with qualitative approach. And data collection techniques in this study are in-depth interviews, direct observation, and documentation. The results of ths research, in marketing efforts, “Embrio”  distro has done the stages of direct marketing as a marketing communication strategy as expected which is personal selling, servivec and layality as a communication strategy. In an effort to build relationships with customers, “Embrio”  distro perform several stages such as: prospecting, calling and sending messages to customers, marketing products and looking for potential customers by using facebook and Instagram also face to face directly, then, emerged patient and presentiment as wrong one intangible method Embryo distro, fostering persuasive relationships with customers, using social media phones as a marketing step to reach a price agreement and use Facebook, Instagram, Blackberry Messenger, whatsapp to support marketing activities